DUKUNGAN SUAMI DALAM PENINGKATAN PRODUKSI ASI : STUDI KASUS DI RS. BHAYANGKARA MAKASSAR - Hestiani K, Dewi; Suriyani, Andi; Karim, Kasmawati; Ajide, Fardi; Syamsul, Tri Damayanty (Bina Generasi : Jurnal Kesehatan, 2025)
The success of exclusive breastfeeding is significantly influenced by the role of husbands in providing support to their breastfeeding wives. This study aims to explore the forms of spousal support and their impact on breast milk production among breastfeeding mothers at Bhayangkara Hospital, Makassar. A qualitative case study approach was employed, involving five postpartum mothers and their husbands as participants. Data were collected through in-depth interviews, observations, and documentation analysis. The results revealed four main forms of support: emotional, instrumental, informational, and appreciation. Emotional support included encouragement and presence during breastfeeding; instrumental support involved assisting with household chores and baby care; informational support involved providing knowledge about breastfeeding; and appreciation was expressed through praise and verbal recognition. All mothers reported a subjective increase in breast milk production, higher confidence, and lower stress levels due to their husbands' involvement. Four out of five participants successfully practiced exclusive breastfeeding. The study also highlights that informational support plays a crucial role in helping mothers make informed decisions about breastfeeding. Unlike previous studies that emphasized only one or two support types, this study shows that a multidimensional support system yields optimal results. Moreover, appreciation—often overlooked in previous research—proved effective in strengthening maternal motivation and emotional wellbeing. This study contributes new insights by emphasizing subjective maternal experiences and local cultural contexts in Eastern Indonesia. The findings suggest that comprehensive husband involvement is crucial for the success of exclusive breastfeeding programs and should be integrated into maternal and child health strategies. Keywords: Husband Support, Exclusive Breastfeeding